Transport Cost for Carbon Removal Projects With Biomass and CO2 Storage - Stolaroff, Joshuah K.; Pang, Simon H.; Li, Wenqin; Kirkendall, Whitney G.; Goldstein, Hannah M.; Aines, Roger D.; Baker, Sarah E. (Frontiers in Energy Research, 2021)
Strategies to remove carbon from the atmosphere are needed to meet global climate goals. Promising strategies include the conversion of waste biomass to hydrogen, methane, liquid fuels, or electricity coupled with CO2 capture and storage (CCS). A key challenge for these projects is the need to connect geographically dispersed biomass supplies with geologic storage sites by either transporting biomass or CO2. We assess the cost of transport for biomass conversion projects with CCS using publicly available cost data for trucking, rail, and CO2 pipelines in the United States. We find that for large projects (order of 1 Mt/yr CO2 or greater), CO2 by pipeline is the lowest cost option. However, for projects that send most of the biomass carbon to storage, such as gasification to hydrogen or electricity production, biomass by rail is a competitive option. For smaller projects and lower fractions of carbon sent to storage, such as for pyrolysis to liquid fuels, CO2 by rail is the lowest cost option. Assessing three plausible example projects in the United States, we estimate that total transport costs range from 24/t-CO2 stored for a gasification to hydrogen project traversing 670 km to 36/t for a gasification to renewable natural gas project traversing 530 km. In general, if developers have flexibility in choosing transport mode and project type, biomass sources and storage sites can be connected across hundreds of kilometers for transport costs in the range of 20-40/t-CO2 stored. Truck and rail are often viable modes when pipelines cannot be constructed. Distances of 1000 km or more can be connected in the same cost range when shared CO2 pipelines are employed.